Students' Perception of Islamic Political Thought Towards Political Participation of New Voters in the 2024 Election - Nafiahdi, Insan Putra; Harahap, Elly Warnisyah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Indonesia's 2024 general election is a watershed moment in the country's political history, with a large number of first-time voters participating. This research aims to determine the factors that influence the participation of first-time voters in elections, including political awareness, access to information, social environment, motivation, and trust in the electoral system. This research uses a qualitative approach, distributing questionnaires to collect data from novice voters in the Islamic Political Thought Study Program. The findings show that political awareness, access to information, and social environment are significant factors influencing first-time voter participation. Apart from that, motivation and trust in the electoral system also play an important role in determining their decision to participate in the election. This study shows. to encourage the participation of first-time voters in the 2024 election and the findings of this research have significant results for the 2024 election among students of Islamic political thought.